Papel dos receptores glutamatérgicos ionotrópicos do hipotálamo dorsomedial na regulação das respostas cardiovasculares e comportamental do quimiorreflexo - Nathalia Teodoro da Silva (2012)
Studies from our laboratory (Queiroz et al., 2011) showed that bilateral microinjection of lidocaine into the DMH reduces the pressor response to chemoreflex. These studies also showed that the bilateral blockade of glutamate receptors in the DMH with kynu renic acid reduces the pressor response and abolishes the behavioral response of chemoreflex. The excitatory amino acid L-glutamate may act through three distinct subtypes of ionotropic receptors: NMDA (N-methyl-D-aspartate), AMPA (-amino-3-hydroxy-5-methyl-4 isoxazolproprionate) and kainate receptors. AMPA and kainate receptors are also classified as non-NMDA receptors. Previous studies have shown that different stimuli may activate only one subtype of ionotropic glutamate receptor in DMH to evoke a specific physiological response. Furthermore, although kynurenic acid is known as a non-selective antagonist at ionotropic glutamate receptors, some studies show that this antagonist is also able to act at nicotinic receptors (Hilmas et al., 2001, Stone, 2007). Based on this evidence, and considering that DMH neurons express nicotinic receptors (Block and Billiar, 1981), the aim of this study was to re-evaluate the role of ionotropic glutamate receptors in DMH and evaluate the relative contribution of NMDA and non-NMDA receptors in the integration of cardiovascular and behavioral responses of the chemoreflex. Wistar rats (270-330 g), were underwent stereotaxic surgery to implant bilateral guide cannulas into the DMH, five days before the experiments, and cannulation of the femoral artery and vein, one day before the experiments to measurement of cardiovascular parameters and systemic administration of drugs, respectively. The experiments were filmed and the behavioral response of the chemoreflex was assessed by the distance traveled by the animal, measured using the MATLAB software. The chemoreflex was stimulated with intravenous injection of KCN (40 µg /0.1 ml) before and after bilateral microinjection of: a) NMDA receptor antagonist (AP-5 100 or 200 pmol/100 nl), b) non-NMDA receptor antagonist (CNQX 100 or 200 pmol/100 nl) or c) the combination of these two antagonists (AP -5 + CNQX 200 pmol/50 nl) into DMH. Furthermore, additional protocols were performed to evaluate the effectiveness of the AP-5 and CNQX antagonists to block NMDA and non -NMDA receptors, respectively. The NMDA agonist (10 pmol/100 nl) was microinjected into the DMH before and after ipsilateral microinjection of AP -5 (100 or 200 pmol/100 nl) and AMPA agonist (3 pmol/100 nl) was microinjected into DMH before and after the microinjection of CNQX (100 or 200 pmol/100 nl). The microinjection of AP-5 at a dose of 100 pmol/100 nl, did not change the cardiovascular (+47 ± 2 vs 15+43 ± 4 mmHg; -236 ± 26 vs -245 ± 30 bpm) and behavioral (+37 ± 5 vs +27 ± 5 cm) and behavioral responses (+ 39 ± 7 vs. +31 ± 6 cm) of the chemoreflex, but was able to significantly reduce the magnitude of cardiovascular (+21 ± 2 vs +10 ± 3 mmHg vs. +138 ± 14 +74 ± 25 bpm) and behavioral (348 ± 106 vs 48 ± 27 cm) responses induced by NMDA agonist. The microinjection of AP-5 at a dose of 200 pmol/100 nl also produced no changes on cardiovascular (+37 ± 1 vs. +39 ± 3 mmHg vs -260 ± 38 -253 ± 44 bpm) and behavioral (49 ± 14 vs. 31 ± 9 cm) responses of the chemoreflex, but abolished the ca rdiovascular (+22 ± 2 vs +2 ± 1 mmHg; +114 ± 7 vs. +8 ± 5 bpm) and behavioral (425 ± 67 vs 0 ± 0 cm) responses induced by NMDA agonist. Similarly, the microinjection of CNQX at a dose of 100 pmol/100 nl, did not change on the cardiovascular (+39 ± 6 vs. +35 ± 7 mmHg, -237 ± 38 vs -260 ± 22 bpm) and behavioral (33 ± 13 vs 27 ± 8 cm) responses of the chemoreflex, but was able to reduce the magnitude of cardiovascular (+20 ± 2 vs +5 ± 2 mmHg vs. +112 ± 5 vs +39 ± 17 bpm) and behavioral (424 ± 70 vs 11 ± 6 cm) responses of the AMPA agonist. The microinjection of CNQX at a dose of 200 pmol/100 nl also did not change the cardiovascular (+43 ± 3 vs +37 ± 3 mmHg, -202 ± 40 vs -167 ± 37 bpm) and behavioral (40 + ± 12 vs 30 ± 13 cm) responses of the chemoreflex, but abolished the cardiovascular (+28 ± 4 vs. +1 ± 1 mmHg, +90 ± 9 vs. +1 ± 1 bpm) and behavioral (327 ± 87 vs 0 ± 0 cm) responses induced by AMPA agonist. However, microinjection of combined antagonists CNQX + AP-5 (200 pmol/50 ml) significantly reduced the magnitude of the pressor (+38 ± 4 vs +21 ± 5 mmHg) and behavioral (40 ± 14 vs 8 ± 5 cm) responses of the chemoreflex. These results show that the isolated blockade of NMDA or non-NMDA receptors of the DMH is not able of producing changes on pressor and behavioral responses of the chemoreflex. However, since the combined blockade of NMDA and non-NMDA of DMH reduced the pressor response and abolished the behavioral response of chemoreflex, it may suggest that these receptors act jointly on the integration of chemoreflex. These data further reinforce the role of excitatory amino acid L -glutamate in neurotransmission of the chemoreflex in DMH.